2011
DOI: 10.1038/eye.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tear protein profile in keratoconus disease

Abstract: Purpose To analyze tear protein profile variations in patients with keratoconus (KC) and to compare them with those of control subjects. Subjects and methods Tears from 12 normal subjects and 12 patients with KC were analyzed by two-dimensional gel electrophoresis (2-DE) and liquid chromatography-mass spectrometry (LC-MS). Analysis of the 2-DE gels was performed using Progenesis SameSpots software (Nonlinear Dynamics). Proteins exhibiting high variation in expression levels (P-value o0.05) were identified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 38 publications
2
52
0
1
Order By: Relevance
“…They found a relative increase in the abundance levels of cathepsin B and decreased levels of polymeric immunoglobulin receptor, α-fibrinogen, cystatin SN, and cystatin S in the tears of subjects with keratoconus, meaning that tear proteins differentially expressed in keratoconus included increased proteases and decreased protease inhibitors. 95 The findings of a lower level of cystatins by Balasubramanian et al 95 confirmed the ones previously reported in 2011 by Acera et al, 96 who compared tears from 12 normal subjects and 12 patients with keratoconus, using two-dimensional gel electrophoresis and liquid chromatography-mass spectrometry, and found a significant decrease in the levels of members of the cystatin family in keratoconus patients. Cystatins are inhibitors of cysteine proteases, also known as thiol proteases, which are enzymes that degrade proteins.…”
Section: Corneal Stroma Compositionsupporting
confidence: 80%
See 3 more Smart Citations
“…They found a relative increase in the abundance levels of cathepsin B and decreased levels of polymeric immunoglobulin receptor, α-fibrinogen, cystatin SN, and cystatin S in the tears of subjects with keratoconus, meaning that tear proteins differentially expressed in keratoconus included increased proteases and decreased protease inhibitors. 95 The findings of a lower level of cystatins by Balasubramanian et al 95 confirmed the ones previously reported in 2011 by Acera et al, 96 who compared tears from 12 normal subjects and 12 patients with keratoconus, using two-dimensional gel electrophoresis and liquid chromatography-mass spectrometry, and found a significant decrease in the levels of members of the cystatin family in keratoconus patients. Cystatins are inhibitors of cysteine proteases, also known as thiol proteases, which are enzymes that degrade proteins.…”
Section: Corneal Stroma Compositionsupporting
confidence: 80%
“…19,20,106,[108][109][110]144 An important decrease in the level of protease inhibitors such as cystatins (inhibitors of cysteine proteases) and TIMP-1 (inhibitor of MMPs) have also been reported. 95,96,101,[129][130][131] The increased activity of several proteolytic enzymes results in higher concentrations of ROS, RNS, cytotoxic aldehydes (CAs) and peroxynitrates (Ps) (which decreases the activity of TIMP-1 and increase MMP-2), 63,143,144,146,149 and given the lower production of SOD 143 possibly related to IL-1α, 158 an environment with high oxidative stress and low pH is formed, causing an increase in the activation of the caspases (caspase-9 and -12), mitochondrial dysfunction (MD), and DNA damage, 156 which eventually lead to increased apoptosis. All of these could probably be the result of a complex interaction of both genetic predisposition and environmental triggering factors, such as eye rubbing and contact lenses wear (the 'two-hit hypothesis') in keratoconus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophoresis [86], protein arrays [87] and various mass spectrometry-related techniques [85,88] have been applied. Various forms of chemical labeling [39,43], SRM/MRM-based targeted proteomics and label free quantification have been used for tear studies but no PRM or SWATH analyses have been carried out so far [89,90].…”
Section: Tear Proteomics As a Tool In Dr Specific Biomarker Studiesmentioning
confidence: 99%